Capital Planning, Selection, and Investment (Integrating Sustainability in Decision-making) - KIMBRO, MARINILKA B. (Archīum Ateneo, 2017)
Inspired by Pope Francis’s call for a new journey that instills the importance of conservation and care for the environment, we propose a practical model that mathematically incorporates sustainability issues into capital planning, selection, and investment. Evidence suggests that managers apply net present value (NPV) methodologies in a way that disadvantages environmentally sustainable investments. If an NPV model does not consider the costs and risks of non-sustainable projects, then the potential benefits of alternative sustainable investments will appear much less valuable than present costs. Sustainable investments also often require larger initial investments with long-term benefits and distant cash flow time horizons that are discounted at exponentially higher rates. Moreover, identified environmental costs and benefits are generally limited to savings associated with energy costs, while hidden reductions in externalities are ignored. Thus, as commonly used, NPV models bias against sustainable alternatives in investment selection. This article integrates accounting, finance, and engineering literatures to develop a model that incorporates sustainability and environmental impacts into capital selection through a life-cycle impact assessment (LCIA) appraisal. We operationalize LCIA so that hidden environmental costs and benefits can be identified, analyzed, and priced, thus resulting in a better prediction of cash flows. The model also integrates environmental risks into the cost of capital by developing a sustainability risk-adjusted discount rate and sustainability-cost NPV that effectively captures the sustainability exposures of capital projects, thus resulting in a risk-adjusted sustainable framework for decision-making.